Early traditions in the Isle of Man - Broderick, George (Studia Celtica, 2022)
This article looks briefly at the significance of the triskele and swastika as sun-symbols in general and their long association with Insular Celtic traditions, and with the Isle of Man in particular, as well as the association of the triskele and other traditions with Manannán - mac Lir (Manannan Beg mac y Leirr in Man) and with Tynwald, the Manx parliament, in Manx tradition over time.
Gesehen am 21.08.2024